Clinical quality registries: urgent reform is required to enable best practice and best care. Issue 1 (18th January 2022) - Brown, Wendy A.; Ahern, Susannah; MacCormick, Andrew D.; Reilly, Jennifer R.; Smith, Julian A.; Watters, David A.
Abstract: Clinical quality registries (CQRs) systematically collect data on pre‐agreed markers of quality of care for a given procedure, that can be reliably and reproducibly defined and collected across multiple sites. Data is then risk adjusted, and comparisons may be used to benchmark performance. These data then inform quality improvement initiatives. CQRs require an overarching independent governance structure and surety of funding. CQRs rely upon whole of population enrolment to minimize the risk of selection bias, and often rely on the secondary use of sensitive health information, meaning that the processes for ethical review and consent to participation are different to clinical trials. Despite several local examples of CQR improving practice in Australia and Aotearoa New Zealand, providing substantial cost–benefit to the community, there remain significant barriers to CQR implementation and functions. These include the difficulty of accurate data capture, lack of a fit for purpose ethical review system, the constraints of existing Qualified Privilege legislations and the need for protected funding. Whilst the Australian Government has released a 10‐year strategy for CQR reform, and the Aotearoa New Zealand Government has included registries in the planned Health New Zealand reforms for the public sector, we believe more urgent implementation of strategies to overcome these barriers is needed if CQRs are to have the impact on quality of care our Communities deserve. Abstract : Clinical Quality Registries (CQR) have been shown to improve the quality of care patients receive in in Australia and Aotearoa New Zealand, providing substantial cost‐benefit to the community. However, there remain significant barriers to CQR implementation and participation. Whilst the Australian Government has released a 10‐year strategy for CQR reform, and the Aotearoa New Zealand Government has included registries in the planned Health New Zealand reforms for the public sector, we believe more urgent implementation of strategies to overcome these barriers is needed if CQRs are to have the impact on quality of care our Communities deserve.